Komunikasi Pemasaran Terpadu Dan Ekuitas Merek Alfamart - Krussell, Jehuda Ghrahito Hutomo; Paramita, Eristia Lidia (Universitas Muhammadiyah Surakarta, 2016)
In past few years, retail business has significantly improved. Company needs marketing strategy to raise their competitiveness and make a good brand equity. One of these strategy that can be used is Integrated Marketing Communication. This study aimed to examine the influence of integrated marketing communication toward brand equity. This study was a quantitative study. The sample of 150 respondents were taken by using purposive sampling. The data analysis used multiple linear regression. These findings showed that dimension of integrated marketing communication consists of Advertising, Sales Promotion, Personal Selling, Public Relation, Direct Marketing, Interactive Marketing, and Corporate Design together influence Alfamart Brand Equity. While partially, only Sales Promotion, Personal Selling, and Corporate Design has significantly influence Alfamart Brand Equity